2022
DOI: 10.1159/000521720
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Induced Mitochondrial Dysfunction of Chondrocytes through Repression of AMPKα-SIRT1-PGC-1α Pathway

Abstract: <b><i>Introduction:</i></b> Our previous studies have demonstrated advanced glycation end products (AGEs) was an important mediator in osteoarthritis (OA) which may induce mitochondrial dysfunction. AMP-activated protein kinase (AMPK), sirtuin 1 (SIRT1), and its downstream target peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) are the critical sensors that regulate mitochondrial biogenesis and have been recognized as therapeutic targets in OA. This study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…538 Notably, the upregulation of PGC-1α by activating the upstream molecule or coactivating the partners, remarkably reverses impaired mitochondrial biogenesis, oxidative stress, and inflammation in osteoarthritis. [539][540][541][542][543][544] Nevertheless, classical drug therapy may be too late to help due to the relatively late diagnosis during the osteoarthritis process. Fortunately, emerging therapies targeting PGC-1α may possess great potential.…”
Section: Pgc-1s In Atherosclerosismentioning
confidence: 99%
“…538 Notably, the upregulation of PGC-1α by activating the upstream molecule or coactivating the partners, remarkably reverses impaired mitochondrial biogenesis, oxidative stress, and inflammation in osteoarthritis. [539][540][541][542][543][544] Nevertheless, classical drug therapy may be too late to help due to the relatively late diagnosis during the osteoarthritis process. Fortunately, emerging therapies targeting PGC-1α may possess great potential.…”
Section: Pgc-1s In Atherosclerosismentioning
confidence: 99%
“…To observe whether Adenosine 5’-monophosphate-activated protein kinase (AMPK) agonist AICAR (2840, TOCRIS, Bristol, UK) could reverse the effect of AGEs, AGEs+AICAR group and BSA+AICAR group were set. Cells were first treated with AGEs for 24 hours then with 10 μmol/L AICAR for another 24 hours, 18 , 19 to test whether post-AGE AMPK activation leads to normalization of Cx43 and Cx40 expression.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) may induce mitochondrial dysfunction in OA chondrocytes. It has been reported that AGEs can induce oxidative stress and chondrocyte apoptosis by down-regulating the AMPKα/Sirt1/PGC-1α signaling ( Yang et al, 2022 ). Collectively, inhibiting redox-sensitive factors implicated in cell death and stimulating antioxidant expression may facilitate chondrocyte survival and promote cartilage integrity ( Figure 1 ).…”
Section: The Interaction Between Oxidative Stress and Oamentioning
confidence: 99%